BCAT1 promotes cell proliferation through amino acid catabolism in gliomas carrying wild-type IDH1 - Tönjes, Martje; Bărbuş, Sebastian Liviu; Park, Yoon Jung; Wei, Wang; Schlotter, Magdalena; Lindroth, Anders M.; Pleier, Sabrina Valesca; Bai, Alfa H. C.; Karra, Daniela; Piro, Rosario M.; Felsberg, Jörg; Addington, Adele; et al. (Nature medicine, 2013)
Here we show that glioblastoma express high levels of branched-chain amino acid transaminase 1 (BCAT1), the enzyme that initiates the catabolism of branched-chain amino acids (BCAAs). Expression of BCAT1 was exclusive to tumors carrying wild-type isocitrate dehydrogenase 1 (IDH1) and IDH2 genes and was highly correlated with methylation patterns in the BCAT1 promoter region. BCAT1 expression was dependent on the concentration of α-ketoglutarate substrate in glioma cell lines and could be suppressed by ectopic overexpression of mutant IDH1 in immortalized human astrocytes, providing a link between IDH1 function and BCAT1 expression. Suppression of BCAT1 in glioma cell lines blocked the excretion of glutamate and led to reduced proliferation and invasiveness in vitro, as well as significant decreases in tumor growth in a glioblastoma xenograft model. These findings suggest a central role for BCAT1 in glioma pathogenesis, making BCAT1 and BCAA metabolism attractive targets for the development of targeted therapeutic approaches to treat patients with glioblastoma.